Humanoid robot acts out phrases as if playing charades. - Wilkins, Alex (New Scientist, 2023)
A recent article in New Scientist discusses a new development in robotics that could lead to machines behaving and communicating more like humans. Researchers at the University of Tokyo used a humanoid robot called Alter3 and the language model GPT-4 to create convincing actions in response to text prompts. By translating requests into a list of actions and then into the Python programming language, the robot was able to perform tasks such as pretending to be a snake or taking a selfie. While there is a delay in the robot's response, the researchers hope that these human-like motions will enhance our interactions with robots.